Simulation Calculations of the Effects of Operation on the Consumption of a Battery Rail Vehicle (Current Problems in Rail Vehicles, 2025)
The article presents key aspects that have an impact on the calculation of traction energy. These include primarily the use of driving without power and the effect of run without power on the consumption and driving time of the vehicle, the effect of the time of stays at stops while the vehicle's auxiliary drives are running, the effect of the use of regenerative braking into the traction battery and its relationship to adherence and to the timetable. In conclusion, the necessary energy reserves in the battery capacity for reliable operation of battery-trolley vehicles are discussed. For a better understanding of the results, the structure of the SW developed at the Faculty of Transport Engineering of the University of Pardubice, is presented.
Keywords: traction calculations; battery power supply; calculation of rail vehicle driving; LFP battery; battery model